Benefit to be a member of professional accounting organization for academicians / Rafizan Abdul Razak and Akma Hidayu Dol@ Abdul Wahid - Abdul Razak, Rafizan; Dol@ Abdul Wahid, Akma Hidayu (Universiti Teknologi MARA, Negeri Sembilan, 2022)
There are many professional and statutory accounting bodies that govern the practice of an accountant worldwide. One of the statutory bodies is Malaysian Institute of Accountant (MIA) which was established under the Accountants Act 1967. The Institute is mainly responsible to regulate and develop the accountancy profession in Malaysia in support of nation building. Currently, there are more than 37,500 members involved in businesses across all industries in Malaysia and around the world. Do you know that even though you as academicians and do not practice as Chartered Accountants in Malaysia, may also have an opportunity to become an associate member of the Institute if they fit the requirement of Section 14(3) of the Act and the applicable Rules. Pursuant to the Act, those who are not eligible to practice as Chartered Accountants in Malaysia, may also be admitted as Licensed accountants and for those who are closely associated with the profession of accountancy or who has participated in the advancement of accountancy training and education may be admitted as Associate members.